PREDICTORS OF HYPERTENSIVE DISORDERS IN PREGNANCY: UTERINE ARTERY DOPPLER AND PLATELET INDICES - Maryam Khalid Jassim Taka; Nighat Fatima; Syeda Maryam Batool; Ayesha Salman; Seema Waheed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Preeclampsia (PE) and Pregnancy-Induced Hypertension (PIH) are significant hypertensive illnesses that occur during pregnancy, leading to substantial morbidity and death among both the mother and the foetus. Timely and precise screening continues to be a clinical obstacle. Objectives: The objective of this study is to conduct a comprehensive review and synthesis of existing literature about the efficacy of uterine artery Doppler and platelet indices in the prediction of hypertensive disorders during pregnancy. Methods: A thorough examination of research evaluating the use of uterine artery Doppler and platelet indicators to predict hypertensive diseases was carried out. The papers included in the analysis exhibited a range of designs, including prospective observational, cohort, and retrospective research methodologies. A total of seven were included in the review according to PRISMA guidelines. Results: Sharma et al. and Abdel Razik et al. (2019) found that uterine artery Doppler and platelet indices were highly effective in predicting early-onset PIH. The Positive Predictive Value (PPV) was 80%, the Negative Predictive Value (NPV) was 94.29%, and the accuracy for the Pi Index was 90%. The methodological issues mentioned by Chakraborty and Saharan (2017) and Udeh et al. (2024) are evident in their respective lower ratings of 6/9 and 5/9, indicating notable areas that need improvement. Their findings revealed a substantial increase in the detection rate, reaching 31.4% (p=0.015), as well as an Area Under the Curve (AUC) enhancement to 0.849 (p=0.015). The studies conducted by Abdel Razik et al. (2019) and Lin et al. (2023) showed varying degrees of bias, although consistently maintained low levels of bias across all categories. This observation indicates a strong level of methodological integrity. Conclusion: The combination of uterine artery Doppler and platelet indicators offers a potentially effective strategy for the timely detection of hypertension during pregnancy. Nevertheless, further investigation is required to enhance prediction models and enhance their suitability for various populations.